“Kinō Nani Tabeta?” Defying the Complexity of Love in Romantic Relationships - Sutanto, Marisa Rianti; Lewerissa, Ethel Deborah; Nangoi, Jessica Priscilla (Lingua Cultura, 2025)
This research aims to understand the concept of love represented in the Japanese movie “Kinō Nani Tabeta?” The movie, released in 2021, tells the story of a middle-aged homosexual couple in Tokyo, Shiro and Kenji, who are the main characters of the movie. This movie was chosen as an object of analysis because, unlike love relationships, which are typically recognized as romantic relationships between individuals of opposite sexes, the love relationships of the main characters are between individuals of the same sex. The method used in this research is phenomenology, which looks at the movie as a subject; as a world that is experienced by the viewer. In the world of “Kinō Nani Tabeta?”, love is a philosophical insight that is contemplated when the viewer is in the world of the movie. Love in “Kinō Nani Tabeta?” can be interpreted through the approaches of Irigaray and Bell Hooks, who understand love in terms of the existence of difference and the awareness of mutuality. The love expressed in this film is a relationship that transcends gender and fosters a familial bond, one based not only on biological ties but also on a commitment that prioritizes equality. “Kinō Nani Tabeta?” shows that the love of homosexual couples is also a love that is the basis of a familial relationship that is not limited to biological ties.